(untitled) - Golub, Bennett W. (New York, 2000)
Counter RISK MANAGEMENT APPROACHES FOR FIXED INCOME MARKETS "Golub-Tilman will, I believe, become an absolutely essential reference text for fixed income portfolio managers, traders, issuers, and scholars. It is comprehensive and clearly written. While rigorous, it is easy to understand because of its many practical examples."- Richard Roll, The Allstate Chair in Finance and Insurance, The Anderson School at UCLA, Past President, American Finance Association "Outstanding and unique! A thorough discussion of the theoretical underpinning of risk management combined with keen insights from a practitioner's perspective. This text will rank among the most essential readings for both market professionals and academics." -Gregory J. Parseghian, Senior Vice President and Chief Investment Officer, Freddie Mac "The most systematic and comprehensive overview of fixed income risk management."-Philippe Jorion, Professor of Finance, University of California-Irvine, Author, Value at Risk: The New Benchmark for Controlling Derivatives Risk "An inside look at approaches to fixed income risk management developed at a leading investment firm. The rigorous presentation covers both theoretical and practical considerations as well as their applications to portfolio management. Very interesting and highly recommended."-Charles W. Grant, Managing Director of Fixed Income, Virginia Retirement System "Few, if any, financial studies have managed to reconcile practical market experience and scientific discipline within such an original approach and with such elegance! An absolute must for anyone in the world of fixed income."-Michele Donegani, Head of Asset Allocation and Manager Selection, European Investment Managers (EIM).
Keywords: Fixed-income securities,Risk management,Chứng khoán có thu nhập cố định,Quản trị rủi ro